2023
DOI: 10.7759/cureus.38586
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Molnupiravir for the Treatment of Mild or Moderate COVID-19 in Adults: A Meta-Analysis

Abstract: The aim of this meta-analysis is to evaluate the efficacy of molnupiravir among mild or moderate COVID-19 patients. This meta-analysis was reported according to the guidelines of Preferred Reporting Items for Systematic Reviews and Meta-Analyses. Two authors independently performed a comprehensive search for relevant studies in PubMed, Cochrane Library, and Web of Science. The keywords used to search for relevant records were “Molnupiravir,” “COVID-19,” and “efficacy.” This meta-analysis included studies that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…While some meta‐analyses found no significant benefit in using molnupiravir to reduce COVID‐19‐related mortality, 21 , 43 , 44 others showed it to be effective in reducing the risk of death in COVID‐19 patients. 45 , 46 Discrepancies in these findings may be attributed to differences in inclusion criteria and the number of included studies. Current data from studies also support the effectiveness of nirmatrelvir/ritonavir and remdesivir treatments in reducing the risk of death in patients with COVID‐19.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While some meta‐analyses found no significant benefit in using molnupiravir to reduce COVID‐19‐related mortality, 21 , 43 , 44 others showed it to be effective in reducing the risk of death in COVID‐19 patients. 45 , 46 Discrepancies in these findings may be attributed to differences in inclusion criteria and the number of included studies. Current data from studies also support the effectiveness of nirmatrelvir/ritonavir and remdesivir treatments in reducing the risk of death in patients with COVID‐19.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the effectiveness of molnupiravir in reducing COVID‐19‐related mortality remains unclear. While some meta‐analyses found no significant benefit in using molnupiravir to reduce COVID‐19‐related mortality, 21,43,44 others showed it to be effective in reducing the risk of death in COVID‐19 patients 45,46 . Discrepancies in these findings may be attributed to differences in inclusion criteria and the number of included studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Molnupiravir is approved for use in non-hospitalized patients at high risk for disease progression, starting within 5 days of the onset of symptoms (269). A metaanalysis (270) showed that patients receiving molnupiravir had reduced all-cause mortality, and risk of hospitalizations, and improved proportions of patients testing negative by day 5 for viral RNA. It is recommended to be used only in situations when both remdesevir and paxlovid are not available.…”
Section: Antiviralsmentioning
confidence: 99%
“…Using antiviral medications to treat patients with COVID-19, especially those with severe symptoms, is recognized as being more effective than utilizing conventional medication [ 1 , 2 ]. Among these is molnupiravir, which can reduce the risk of all-cause death and enhance the proportion of patients with negative virus status in patients with mild or moderate severity [ 3 , 4 ]. Remdesivir, which operates by inhibiting RNA-dependent RNA polymerase (RdRp) using the same mechanism of action, is recognized as being beneficial in enhancing clinical condition, lowering mortality rates, and circumventing the need for high-flow supplemental oxygen and invasive mechanical ventilation in hospitalized patients [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%